Thyroid Hormone-Responsive Genes in Primary Cultures of Rat Hepatic Cells - Nariaki Fujimoto; Shigeyuki Kitamura (DNA)
Background/Objectives: Thyroid hormones are key regulators in hepatic metabolic pathways. Although they regulate various hepatic genes, only a few are known to be under direct transcriptional regulation through thyroid hormone receptors. To better understand the roles of thyroid hormones in the liver, it is critical to identify thyroid hormone-responsive genes at the cellular level. Methods: A cDNA microarray analysis was applied to primary cultures of rat hepatic cells treated with triiodothyronine (T3) at 10−9 M for 24 h to identify the differentially expressed genes. The identified gene expressions were further examined in vivo using F344 rats. The reporter gene assay was performed to investigate the transcriptional activity of the upstream region of the gene. Results: A limited number of genes were listed, and only three of them, pyridoxal kinase (Pdxk), phosphoenolpyruvate carboxykinase 1 (Pck1), and solute carrier family 17 member 2 (Slc17a2), were confirmed to be upregulated by quantitative RT-PCR. The mRNA expression of these genes increased in the livers of F344 rats after T3 injection, suggesting the physiological relevance in vivo. There are two partially conserved thyroid hormone-responsive elements (TREs) in the upstream region of the rat Pdxk gene. The reporter gene assay indicated that an imperfect TRE (5′-gGGTCAxxxxAGGaCt-3′) located at −2146 was sufficient for the thyroid hormone-induced transcription of the gene. Conclusions: The present study identified novel T3-responsive genes, pdxk and Slc17a2. Promoter analyses showed that a single TRE in the pdxk gene accounts for the transcriptional regulation by T3.